Physiological factors in the production of cabbage under no-tillage - Marasca, Indiamara; da Silva de Jesus, Ereni; Jussiê da Silva Solino, Antônio; Perreria Bravo, Juliana; de Souza Novak, Rosilei; Moraes Tavares, Rose Luiza (Comunicata Scientiae, 2022)
The no-till system promotes benefits that extend not only the characteristics of soil improvement, interfering in the quality and productivity of the plants, thus improving physical, chemical, and biological attributes of the crop and resulting in profitability to the producer. The present study evaluated the agronomic development of cabbage according to different cover plants. The experiment was performed in the field, in the Vegetable sector of the University of Rio Verde - UniRV, Rio Verde, GO. The cover plants used were millet (Pennisetum americanum (L)), sunflower (Helianthus annuus), brachiaria (Brachiaria decumbens), and crotalaria (Crotalaria juncea). The studied greeneries were cabbage (Brassica oleracea), Astrus plus hybrid. The parameters evaluated to analyze the physiological development were: the plants’ height, number of leaves, and cabbage diameter. The results were submitted to the descriptive statistical method with analysis of means, covariances, and correlations, using the Matlab program. Plant growth data were submitted to the analysis of variance, and when significant, the cover plant factor was compared by Fisher’s test, and the factor days after planting was analyzed by regression. The cabbage showed a higher mean height (cm), leaves, and diameter with the sunflower covering plant. The millet was the best plant to increase the cabbage’s mean productivity.